Monetary Policy Implementation and Liquidity Management of the Czech Banking System - Karel Brůna (European Financial and Accounting Journal, 2010)
Implementation of monetary policy assumes that monetary policy instruments stabilize O/N interest rates to the proximity of main policy rate to archive monetary targets. The function of stabilizing mechanism is based on simple rule that the volume of liquidity in the banking system is held in line with the demand of banks for reserves. In this paper main factors of banking system liquidity are analyzed in the context of bank's imperfect intertemporal substitution of reserves and with respect to predictibility of O/N interest rates volatility. Analysis of O/N PRIBOR and CZEONIA reference interest rates prove Czech National Bank's ability to stabilise O/N interest rates disregard overall excess liquidity in the banking system. It also identified structural changes acting in the money market like reduced instability of demand for reserve and decreased volatility of O/N interest rates due to introduction of credit facility or increased volatility of the spread between O/N interest rates and repo rate due to reduction of frequency of repo tenders. Rapid increase in the volatility of differences between OMO target and bank's supply of excess reserves is also resulting in the weakening of a direct relationship between O/N PRIBOR dynamics and repo tenders.
Keywords: E43; G12; 650; Monetary policy implementation; Liquidity management; Interest rates